How to Redistribute the Revenues from Climate Policy? A Dynamic Perspective with Heterogeneous Households - Ulrich Eydam; Francesca Diluiso (ZBW - Leibniz Information Centre for Economics, 2022)
In light of climate change mitigation efforts, revenues from climate policies are growing, with no consensus yet on how they should be used. Potential efficiency gains from reducing distortionary taxes and the distributional implications of different revenue recycling schemes are currently debated. To account for households heterogeneity and dynamic trade-offs, we study the macroeconomic and welfare performance of different revenue recycling schemes using an Environmental Two-Agent New-Keynesian model, calibrated on the German economy. We find that, in the long run, welfare gains are higher when revenues are used to reduce distortionary taxes on capital, but this comes at the cost of higher inequality: while all households prefer labor income tax reductions to lump-sum transfers, only financially unconstrained households are better off when reducing taxes on capital income. Interestingly, we find that over the transition period relevant to meet short-medium run climate targets, labor income tax cuts are the most efficient and equitable instrument.
Keywords: E62; H23; H31; Q58; 330; double dividend; E-DSGE; environmental tax reform; non-Ricardian households; revenue recycling; redistribution